Peran Metformin sebagai Terapi pada Kanker Kolorektal - Puji Indah Permatasari (Medula, 2020)
In Indonesia, based on WHO data in 2014, colorectal cancer ranks second in men and third in women. Diet and lifestyle factors are risk factors for colorectal cancer. Limiting the consumption of cooked meat and red meat, replacing it with fish as an alternative source of protein and avoiding cooking meat at high temperatures are some strategies to reduce the risk of colorectal cancer.3,4 Insulin is thought to trigger tumorigenesis either directly by affecting epithelial tissue through its interaction in insulin / insulin-like growth factor receptors, or indirectly through its effect on other modulators, such as sex hormones and adiponectin. Metformin is a drug that is believed to have properties to treat diabetes since the 17th century. Retrospective studies show that metformin is also associated with a reduced risk of cancer, suggesting a potential role as an anticancer agent.2 The mechanism of metformin as a preventive or adjuvant therapy in colorectal cancer is based on inhibition of growth and proliferation of cancer cells through its main mechanism, affecting the AMPK / mTOR pathway. This is the basis for the potential of metformin to be used as a preventive therapy or adjuvant therapy in cancer, especially colorectal cancer.